The Effectiveness of Technical Guidance for Entrepreneurs in Small and Medium Enterprises in Facing Halal Certification - Siska, Siska; Rahmi, Hanifah; Situmorang, Almawati (UIN Sunan Gunung Djati Bandung, 2020)
Indonesia is the largest Muslim population country in the world, so the market demand for halal products is enormous. However, in fact, there are not many business actors who submit and have halal certificates, especially in small and medium enterprises. This problem can be due to lack of information and sufficient understanding to apply for a halal certificate. The aim of the research is to give technical guidance for preparing halal certification process. The manual method is used to provide training on the halal guarantee system for the preparation of the halal assurance system (HAS). The workshop began with a pre-test and then the presentation of halal assurance system material, the guidance on how to prepare and discussion. All the activities were done by online (WhatsApp group and zoom meeting). The training ended with the post-test to assess the improvement of knowledge of the. To analyze the difference, we used a paired T-test statistical method. The result of this research shows an increasing understanding of participants (p<0,05) through the comparison between before and after training. These activities conclude that the practice of technical guidance for facing halal certification is beneficial for small and medium enterprises in improving knowledge and capability of the halal certification process.